School refusal and cognitive anxiety (European Journal of Health Research, 2020)
There are a number of factors that can have a negative impact on academic achievement, as well as on positive social and school adaptation. One of these is school anxiety at the cognitive level, known as negative thoughts and images of school situations that trigger avoidance and/or escape from the clasroom of school institution. The objective of this study was to analyze differences in school refusal based on high and low scores in cognitive anxiety, in a sample of 1588 adolescents between 12 and 18 years of age, enrolled in secondary in high school courses. To this end, the cognitive scale of the Inventario de Ansiedad Escolar para Educación Secundaria (IAES) and the School Refusal Assessment Scale-Revised (SRASR) were applied. The findings of the study show that adolescents with high cognitive anxiety, unlike their peers with low scores, score significantly higher in three of the four dimensions of SRAS-R. In conclusion, these results point the negative consequences for the school and psychosocial adaptation of students, in line with previous literatura, which supports the need to design interventions that minimize the problem.